2021
DOI: 10.1093/mnras/stab1801
|View full text |Cite
|
Sign up to set email alerts
|

The integrated three-point correlation function of cosmic shear

Abstract: We present the integrated 3-point shear correlation function iζ± — a higher-order statistic of the cosmic shear field — which can be directly estimated in wide-area weak lensing surveys without measuring the full 3-point shear correlation function, making this a practical and complementary tool to 2-point statistics for weak lensing cosmology. We define it as the 1-point aperture mass statistic Map measured at different locations on the shear field correlated with the corresponding local 2-point shear correlat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 83 publications
3
56
0
Order By: Relevance
“…Interestingly, we will also see that the addition of 𝜁 ± helps to tighten the constraints on the baryonic feedback parameters themselves, which strengthens the opportunity for cosmic shear data to constrain not only cosmology but also astrophysical models of AGN feedback (Huang et al 2021). This provides further motivation to include 𝜁 ± information in constraint analyses of cosmic shear data, reinforcing the promising potential of this statistic that Halder et al 2021 had highlighted before.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…Interestingly, we will also see that the addition of 𝜁 ± helps to tighten the constraints on the baryonic feedback parameters themselves, which strengthens the opportunity for cosmic shear data to constrain not only cosmology but also astrophysical models of AGN feedback (Huang et al 2021). This provides further motivation to include 𝜁 ± information in constraint analyses of cosmic shear data, reinforcing the promising potential of this statistic that Halder et al 2021 had highlighted before.…”
Section: Introductionsupporting
confidence: 64%
“…This semi-analytical approach takes as inputs the nonlinear matter power spectrum and its response functions to long-wavelength perturbations, which are much easier to predict and calibrate using 𝑁-body simulations compared to the full nonlinear matter bispectrum. One of our main results in this paper is the demonstration of the accuracy of the response approach to describe the integrated shear 3PCF 𝜁 ± (𝛼) deep in the 1 We drop the letter 𝑖 from the notation 𝑖𝜁 ± used in Halder et al 2021 to avoid confusion with the imaginary unit 𝑖 = √ −1. 2 This statistic was first introduced by Chiang et al (2014Chiang et al ( , 2015 in the context of three-dimensional galaxy clustering analyses, where it admits a similar physical interpretation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been found that these statistics do not capture all the information from the non-linear and non-Gaussian regime of the WL field. This has led to an array of work attempting to extract this additional information, including non-Gaussian 𝑁-point statistics such as the 3-point function and its Fourier transform the angular bispectrum (Fu et al 2014;Coulton et al 2019;Halder et al 2021;Halder & Barreira 2022), Minkowski functionals (Maturi et al 2010;Munshi et al 2011;Kratochvil et al 2012;Petri et al 2013;Marques et al 2019;Gatti et al 2021), convergence peak and minima statistics (Jain & Van Waerbeke 2000;Yang et al 2011;Liu et al 2015;Kacprzak et al 2016;Li et al 2019;Martinet et al 2021;Zürcher et al 2021;Harnois-Déraps et al 2021), as well as machine learning methods (Gupta et al 2018;Fluri et al 2019;Ribli et al 2019;Matilla et al 2020;) and related techniques (Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 99%